Ministry Of Supply and Internal Trade Ministerial Decree No. 85 Of The Year 2016 Issued on 7/4/2016 On Regulating the Circulation of Packed Milks = وزارة التموين والتجارة الداخلية قرار وزارى رقم 85 لسنة 2016 صادر بتاريخ 7/4/2016 فى شأن تنظيم تداول الألبان المعبأة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic